Implementasi Model Brain Based Teaching untuk Meningkatkan Kamampuan Berpikir Komputasi Tahfiz Al-Qur’an - Fikri Muhammad; Sarwo Derta (Jurnal Ilmiah Edukatif, 2024)
The background of this research is the low thinking ability of students in storing memories of Al-Qur'an tahfizh like a computer, even though the human brain is more powerful than a computer. The aim of this research is to determine the implementation of the brain based teaching model to improve the computational thinking skills of tahfizh Al-Qur'an students in class X MAN 5 Agam. This research method is classroom action research (PTK). The instruments used in this research were tests in the form of pre-test and post-test questions, observations of teacher performance and student performance during the implementation of learning and documentation in the form of lesson plans and photos of activities. This research was carried out in 2 cycles. The data analysis used is quantitative data analysis and qualitative data analysis. Quantitative data analysis is used to analyze average test results using a brain-based teaching model to improve computational thinking skills in understanding the Al-Qur'an. The steps to determine the average test result score are the number obtained by students (∑×) divided by the number of students (n). Meanwhile, qualitative data analysis is used to provide information that describes the improvement in teacher performance results and student activities using the brain based teaching model which is applied during the implementation of learning using observation sheets. Data collected from observation sheets was analyzed qualitatively in the form of percentages (%). This shows that the results of cycle I are 68%, which means it is in the "sufficient" category and has not yet reached classical completion. Meanwhile, in cycle II the results were 86%, which means it was in the "very good" category and had achieved classical completion.